Prevalence and Associated Factors of Peer Victimization (Bullying) among Grades 7 and 8 Middle School Students in Kuwait - Ahmad J. Abdulsalam; Abdullah E. Al Daihani; Konstantinos Francis (International Journal of Pediatrics)
Background. Peer victimization (bullying) is a universal phenomenon with detrimental effects. The aim of this study is to determine the prevalence and factors of bullying among grades 7 and 8 middle school students in Kuwait. Methods. The study is a cross-sectional study that includes a sample of 989 7th and 8th grade middle school students randomly selected from schools. The Revised Olweus Bully/Victim Questionnaire was used to measure different forms of bullying. After adjusting for confounding, logistic regression identified the significant associated factors related to bullying. Results. Prevalence of bullying was 30.2 with 95% CI 27.4 to 33.2% (3.5% bullies, 18.9% victims, 7.8% bully victims). Children with physical disabilities and one or both non-Kuwaiti parents or children with divorced/widowed parents were more prone to be victims. Most victims and bullies were found to be current smokers. Bullies were mostly in the fail/fair final school grade category, whereas victims performed better. The logistic regression showed that male gender (adjusted odds ration = 1.671, p=0.004), grade 8 student (adjusted odds ratio = 1.650, p=0.004), and student with physical disabilities (adjusted odds ratio = 1.675, p=0.003), were independently associated with bullying behavior. Conclusions. There is a need for a school-wide professional intervention program and improvement in the students’ adjustment to school environment to control bullying behavior.